Method selection of microseismic studies depending on the problem being solved - Biryaltsev E.V.; Kamilov M.R. (Общество с ограниченной ответственностью «Георесурсы», 2018)
The article compares two methods of microseismic studies of the maximum likelihood method and the Capon method for detecting the position of microseismic event when observed from the surface in the conditions of the developed deposit or by monitoring the hydraulic fracturing. The results of computational experiments for determining the accuracy of localization of model microseism in space, as well as for various noise levels, for various types of microseismic events and for the allocation of recurring events are presented. Based on the results of the experiments, the conclusion is drawn that the problems of identifying non-recurring events are more confidently solved by maximum likelihood methods, while for the detection of zones of increased fracturing, the method of Capon is best suited.
Keywords: hydraulic fracturing monitoring; natural fracturing monitoring; microseismic events; maximum likelihood method; superresolution method; Capon method; seismic moment tensor